Synergistic copper-aminocatalysis for direct tertiary -alkylation of ketones with electron-deficient alkanes - Shan, Qi-Chao (2024)
In this study, a novel approach for the tertiary α-alkylation of ketones using alkanes with electron-deficient C─H bonds is presented, employing a synergistic catalytic system combining inexpensive copper salts with aminocatalysis. This methodology addresses the limitations of traditional alkylation methods, such as the need for strong metallic bases, regioselectivity issues, and the risk of over alkylation, by providing a high reactivity and chemoselectivity without the necessity for pre-functionalized substrates. The dual catalytic strategy enables the direct functionalization of C(sp3)─H bonds, demonstrating remarkable selectivity in the presence of conventional C(sp3)─H bonds that are adjacent to heteroatoms or π systems, which are typically susceptible to single-electron transfer processes. The findings contribute to the advancement of alkylation techniques, offering a practical and efficient route for the construction of C(sp3)─C(sp3) bonds, and paving the way for further developments in the synthesis of complex organic molecules.